1998
DOI: 10.1542/peds.102.6.1358
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the Ketogenic Diet—1998: A Prospective Evaluation of Intervention in 150 Children

Abstract: The ketogenic diet should be considered as alternative therapy for children with difficult-to-control seizures. It is more effective than many of the new anticonvulsant medications and is well tolerated by children and families when it is effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
375
3
21

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 561 publications
(417 citation statements)
references
References 17 publications
18
375
3
21
Order By: Relevance
“…The KGD has a greater efficacy in younger children, with widespread onset seizures, either multifocal or generalized, rather than with a well-defined focal onset (12). However, with starvation and ketosis, patients are predisposed to metabolic acidosis during treatment with the KGD, especially during induction (9).…”
Section: Discussionmentioning
confidence: 99%
“…The KGD has a greater efficacy in younger children, with widespread onset seizures, either multifocal or generalized, rather than with a well-defined focal onset (12). However, with starvation and ketosis, patients are predisposed to metabolic acidosis during treatment with the KGD, especially during induction (9).…”
Section: Discussionmentioning
confidence: 99%
“…The ketogenic diet (KD) is an established nonpharmacologic treatment for patients with intractable epilepsy (1,2) and was designed to mimic the biochemical changes seen upon fasting, specifically the formation of ketone bodies: ␤-hydroxybutyrate (BHB), acetoacetate (ACA), and to a lesser extent, acetone. Despite decades of clinical experience with the KD, the mechanisms underlying its anticonvulsant activity remain poorly understood.…”
mentioning
confidence: 99%
“…Patients who initiated the classic ketogenic diet at another institution but were then treated at the Johns Hopkins Hospital were included. 2 Records were reviewed for patient demographics, efficacy (parental seizure calendars), side effects, and most recent laboratory values (including lipid profiles, liver enzymes, urine calcium:creatinine ratios, and ketosis level). After 2 years on the ketogenic diet, follow-up visits and laboratory studies were typically obtained every 6 to 12 months.…”
Section: Methodsmentioning
confidence: 99%
“…1 Previous studies have demonstrated that the efficacy of the diet in providing seizure control for children with difficult-to-manage seizures is at least equal to many of the newer anticonvulsant medications and often allows a decrease in medication. 2,3 Most epilepsy centers advocate use of the diet for 2 to 3 years if it controls seizures, followed by a gradual discontinuation in a manner similar to the withdrawal of anticonvulsants. Effects of the diet have been reported in patients who were on it for as long as 3 to 6 years' duration.…”
mentioning
confidence: 99%